An Act in Addition to the several Acts already made for the prudent Storage of Gun-Powder within the Town of Boston, ch. XIII, 1783 Mass. Acts pp. 218-219 - (:unkn) unknown (General Publisher, 1783)
Created a fine of ten pounds for individuals creating the fire hazard of having a loaded cannon, swivel, mortar, howitzer, cohorn, firearm loaded with gun powder, bomb, grenade, or other iron-shell in a dwelling house.
--
Keywords: GUN POWDER POSSESSION